ANALISIS PENERAPAN PERATURAN WALIKOTA MAKASSAR NO 40 TAHUN 2015 TENTANG PENETAPAN NILAI SEWA REKLAME PADA CV IQRA’99 MAKASSAR - Ainun Nur Khalizah Rosali; Sri Nirmala Sari; Nurul Afifah (Politeknik Bosowa, 2021)
The imposition of advertisement tax shall be carried out on the person or entity that manages the advertisement. The basis for the imposition of advertisement tax is the Advertisement Rental Value, which is determined through the Billboard Tax Object Sales Value and the Strategic Value of Advertising Signs. This research was conducted at CV Iqra '99 Makassar which is a company in the field of Printing and Digital Printing with a qualitative descriptive approach that processes primary and secondary data. The results showed that CV Iqra 99 Makassar determined the Billboard Tax Object Sales Value by reporting to the Makassar City Revenue Service regarding the size of the billboard, the type of billboards and the advertisement period. Meanwhile, to determine the Strategic Value of the Iqra 99 Makassar Billboard Installation Makassar will report the Installation Location which is the customer's order point. Application of Makassar Mayor Regulation No. 40 of 2015 concerning Determination of Billboard Rental Value is expected to be able to help the billboard entrepreneurs in the process of calculating the amount of advertisement tax and to be an important part of enforcing tax regulations in Makassar.Keywords: Advertisement Tax, Advertisement Rental Value, NJOPR, NSPR